2015
DOI: 10.1038/srep11495
|View full text |Cite
|
Sign up to set email alerts
|

Use of nicorandil is Associated with Increased Risk for Gastrointestinal Ulceration and Perforation- A Nationally Representative Population-based study

Abstract: Nicorandil is a vasodilatory drug used to relieve angina symptoms. Several healthcare products regulatory agencies have issued a warning associating the use of nicorandil and gastrointestinal (GI) ulceration. We aimed to evaluate the association between use of nicorandil and GI ulceration/perforation. A population-based cohort study involving 1 million randomly sampled participants in Taiwan’s National Health Insurance Research Database was carried out. We estimated the association between use of nicorandil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(51 reference statements)
0
7
0
1
Order By: Relevance
“…Depuis 2002, des localisations extra-orales des ulcérations dues au nicorandil ont été rapportées, principalement au niveau du tractus gastro-intestinal et de la zone péri-anale [22,23], de la cornée et de la conjonctive [24], de l'appareil génital [25] et de la peau [26]. Les lésions du tractus digestif peuvent être responsables d'hémorragies, fistules et perforations, complications graves, nécessitant une prise en charge urgente et adéquate.…”
Section: Discussionunclassified
“…Depuis 2002, des localisations extra-orales des ulcérations dues au nicorandil ont été rapportées, principalement au niveau du tractus gastro-intestinal et de la zone péri-anale [22,23], de la cornée et de la conjonctive [24], de l'appareil génital [25] et de la peau [26]. Les lésions du tractus digestif peuvent être responsables d'hémorragies, fistules et perforations, complications graves, nécessitant une prise en charge urgente et adéquate.…”
Section: Discussionunclassified
“…The chance of this rare but potentially severe side effect increases with higher doses and long term use of this drug, and heals after drug withdrawal. A recent population-based study of this drug’s association with GI ulceration or perforation has been reported 75. This study, based on more than 600,000 randomly selected patients, found a 43% increase in the risk of GI ulceration and a 60% increase in the risk of GI perforation.…”
Section: Drug Influencing K+ Channels and Notable Ulceration As Theirmentioning
confidence: 97%
“…Patients may present with ulcers, which are usually painful, in the mouth, around the anus, or on the cornea, skin, or genitalia 214151617. Those with ulcers in the bowel may present with gastrointestinal haemorrhage.…”
Section: How Do Patients With This Adverse Reaction Present?mentioning
confidence: 99%